Hubungan Pengetahuan Gizi dan Pola Makan dengan Kejadian Overweight pada Remaja Putri - Cikita Dwi Rahmadani; Tina Yuli Fatmawati; Aisah Aisah; Andicha Gustra Jeki; Nel Efni (Jurnal Akademika Baiturrahim Jambi, 2026)
Overweight refers to a condition in which an individual’s body weight surpasses the normal threshold. Prevalence of overweight among adolescents in Jambi City has reached 8.13%. Insufficient nutritional knowledge and poor dietary practices greatly influence health outcomes and are major contributors to overweight, especially among Adolescent girl. This study sought to examine the association between nutrition-related knowledge and eating patterns with the occurrence of overweight among female students at SMAN 4 Jambi City in 2025. The study population comprised all grade X and XI female students, totaling 471 individuals, while the final sample included 83 respondents chosen through proportional random sampling. Data collection instruments consisted of a structured interview questionnaire combined with anthropometric assessments. Data were analyzed using univariate and bivariate techniques, employing the chi-square test. Findings revealed that a considerable proportion of respondents demonstrated low levels of nutritional knowledge (35.0%), more than half displayed unhealthy dietary habits (51.8%), and the majority fell within the normal weight range (54.2%). Statistical analysis confirmed a significant correlation between nutritional knowledge (p = 0.000) and dietary habits (p = 0.010) with overweight incidence. The study recommends enhancing nutrition and health education in schools, providing healthier food options in school canteens, and encouraging students to engage in regular physical activities. It is recommended that schools enhance nutrition and health education, provide healthy canteen options, and promote regular physical activity among students.